Review of the Neotropical genera Barra Jordan and Brevibarra Jordan, with description of a new species of Barra from Nicaragua, notes on the tribe Piesocorynini Valentine, and new records of Brevibarra from Brazil and Ecuador (Coleoptera: Anthribidae) - Trýzna, Miloš; Carrasco, Juan Carlos; Blažej, Lukáš (Zootaxa, 2022)
The Neotropical genera Barra Jordan, 1904, and Brevibarra Jordan, 1906 (Anthribidae: Anthribinae: Piesocorynini Valentine, 1960) are reviewed. A key to obviously similar genera of this tribe, based on mandible shape, is proposed. A new species, Barra baruskae sp. nov., from Nicaragua is described, male genitalia are studied and illustrated. A key to the now three known species of Barra, and colour photographs are provided. New data on the distribution of Brevibarra scotosagis Jordan, 1906 from Brazil and Ecuador, including illustration of genitalia and colour habitus photographs, are provided.